Long term outcomes associated with the use of perioperative systemic chemotherapy on low grade appendiceal mucinous neoplasms with pseudomyxoma peritonei treated with cytoreductive surgery and hyperthermic intraperitoneal chemotherapy - Samantha M. Ruff; Gyulnara Kasumova; Manoj Palavalli; Oliver S. Eng; Laura Lambert; Callisia Clarke; Sameer Patel; Jula Veerapong; Keith Fournier; Daniel Abbott; Charles Staley; Travis Grotz; et al. (Frontiers in Oncology)
IntroductionLow grade appendiceal mucinous neoplasms (LAMN) are indolent tumors that lack invasive potential but may present as pseudomyxoma peritonei. Cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) significantly improves both overall and recurrence free survival. While systemic chemotherapy is generally considered ineffective for LAMN, little literature is available to support this notion. We evaluated outcomes for individuals with LAMN who did and did not receive systemic chemotherapy in combination with CRS+HIPEC.MethodsA multicenter retrospective cohort study was performed using the US HIPEC Collaborative that included patients with LAMN who underwent CRS+HIPEC. The overall survival (OS) and recurrence-free survival (RFS) of patients who did and did not receive systemic chemotherapy were compared. Survival and variables associated with survival were evaluated with the Kaplan-Meier analysis and cox regression, respectively.ResultsAmong the 529 included patients with LAMN, 63 (11.9%) received systemic chemotherapy and CRS+HIPEC, while 466 (88.1%) were treated with only CRS+HIPEC. Patients selected for systemic chemotherapy had a higher burden of disease (mean peritoneal cancer index: 18.8 +/- 8.6 versus 14.3 +/- 8.8, p<0.001). Patients who were not treated with chemotherapy had better mean OS and RFS (OS: 104.3 +/- 6.2 months, RFS: 84.9 +/- 6.6 months) compared to those who underwent systemic chemotherapy (OS: 70.2 +/- 6.8 months, RFS: 38 +/- 5.9 months, p<0.001). Increasing pre-operative CEA level (HR 1.012, p<0.001), higher completeness of cytoreduction score (reference CCR 0, CCR2 HR 34.175, p=0.001 and CCR3 HR 52.041, p=0.001), and treatment with systemic chemotherapy (HR 4.196, p=0.045) were associated with worse OS.ConclusionsIn this multicenter retrospective study, the receipt of perioperative chemotherapy was associated with worse long-term outcomes among patients with LAMN undergoing CRS-HIPEC. Systemic chemotherapy may lead to patient deconditioning and contribute to worse long-term outcomes. It should not be recommended outside of a clinical trial.